1994
DOI: 10.1016/0014-5793(94)00557-5
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Cloning of an orphan opiate receptor gene family member and its splice variant

Abstract: Radioligand binding and cDNA homology studies have suggested the existence of opiate receptors distinct from the recently-cloned p, S and K receptors. XORlS, a rat brain cDNA whose predicted translation product displays 67-72% homology with those encoded by ~1, 61 and ~1 opiate receptor cDNAs, was constructed from two partial cDNAs identified through cDNA homology approaches. A longer XORlL variant of this cDNA was also identified by polymerase chain reaction studies using genomic DNA and cDNA from brain and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
177
0
4

Year Published

1996
1996
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(186 citation statements)
references
References 19 publications
5
177
0
4
Order By: Relevance
“…The transcript encoding the NC-receptor is found not only in the central nervous system (Darland & Grandy, 1998) but also in peripheral tissues such as rat intestine, skeletal muscle, vas deferens, spleen and lymphocytes (Wang et al, 1994;Peluso et al, 1998;Wick et al, 1995). NC is reported to inhibit electrically induced contractions in several peripheral isolated preparations (see for review).…”
Section: Introductionmentioning
confidence: 99%
“…The transcript encoding the NC-receptor is found not only in the central nervous system (Darland & Grandy, 1998) but also in peripheral tissues such as rat intestine, skeletal muscle, vas deferens, spleen and lymphocytes (Wang et al, 1994;Peluso et al, 1998;Wick et al, 1995). NC is reported to inhibit electrically induced contractions in several peripheral isolated preparations (see for review).…”
Section: Introductionmentioning
confidence: 99%
“…These opioid receptors are all coupled to the inhibitory G protein (Gi) and negatively regulate adenylyl cyclase [1]. Recently, another Gi protein coupled receptor, opioid receptor-like receptor (ORLi), has been cloned from brain [2][3][4][5][6][7][8]. Its endogenous specific agonist nociceptin/orphanin FQ (OFQ) has also been identified [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the three major types of opioid receptors, μ, δ and κ (review in [1]), a novel receptor (ORLi, opioid receptor-likei) was identified on the basis of its homology with the amino acid sequence of opioid receptors [2][3][4][5][6][7][8]. The ORLi receptor has a very low affinity for traditional opioid peptides (dynorphins, endorphins, and enkephalins).…”
Section: Introductionmentioning
confidence: 99%